Integrating a Mobile App into Pharmacist-Led Patient Education to Enhance Insulin Pen Self-Administration: A Pre-Experimental One-Group Pretest–Posttest Study - Muhammad Thesa Ghozali; Bagas Dwi Nugroho; Anita Agustina Styawan; Satibi Satibi; Gerhard Fortwengel (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2026)
Introduction: Objectives This study was conducted to assess the impact of adding mobile health (mHealth) application on pharmacist-mediated patient counseling to improve accuracy of insulin pen self-administration skills among diabetic patients. Introduction Every day, diabetes mellitus (DM) remain one of the worlds biggest health problems where insulins therapy acts among the mainstay in treating type 1 and ineffective treatment for type 2 diabetes mellitus (T2DM). Insulin pens have increased convenience and adherence to insulin therapy compared with traditional vials and syringes; however, administration errors are still prevalent. These errors typically due to incorrect priming, wrong injection angle or failure to discharge air bubbles can lead to hypoglycemia, hyperglycaemia, and loss of glycemic control, with consequent negative impact on therapeutic outcomes. Although the results provide evidence of substantial improvement in dosing accuracy of insulin, causal inference and generalizability are limited by the single-group pretest–posttest design. Controlled studies moving forward are required to validate these results. The goal of this study was to determine if the addition of these mHealth technologies in pharmacist-led education could help us fill this important procedural gap. Methods: Between December 2023 and May 2024, this study took place in the outpatient clinic of PKU Muhammadiyah Gamping Hospital, Yogyakarta, Indonesia as a pre-experimental, one-group pretest–posttest study. Hundred adult diabetic patients were selected. Structured questionnaires and direct observations based on a standardized insulin pen checklist were used to collect the data. Ethics approval was obtained from Health Research Ethics Committee of PKU Muhammadiyah Gamping Hospital, and all individuals provided written informed consent. Results: At baseline, 29% of participants achieved high proficiency but post-intervention all (100%) achieved this level. Mean accuracy score significantly improved, from 10.28 (SD = 1.36) to 14.12 (SD = 1.03) (p <0.001). Procedural enhancements were to mix insulin and remove air bubbles. Conclusion: Pharmacist-led education with mHealth integration, the application of mobile technology in health monitoring, represents a novel and potentially generalisable approach in efforts to improve practices of insulin self-administration.